Coplanar band-pass filter for GSM applications based on novel metamaterial unit cell - Nasiri, Badr; Ennajih, Abdelhadi; Errkik, Ahmed; Zbitou, Jamal; Derri, Mounir (International Journal of Engineering and Technology, 2019)
This letter presents a novel compact bandpass filter. The proposed coplanar filter is intended to be a good solution for GSM applications corresponding to the 1.8GHz resonance frequency. The design of this circuit was carried out in two main stages. The first is the choice and proposition of a new metamaterial resonator with unusual characteristics. Then, our resonator is implemented in the structure using bandwidth adjustment methods in order to improve the reflection and transmission coefficient matching in the desired range of frequencies and the two rejection bands. By using different techniques of miniaturization and optimization, we have obtained a miniaturized final circuit which is implemented on a FR4 epoxy substrate. The simulated results are carried out by using CST Microwave and ADS Agilent. They illustrate that this filter achieves very good electrical performances in the passband with a low insertion loss of 0.3 dB. Moreover, two transmission zeros are noticed in the rejected bands.Â